Separability in Riemannian Manifolds - Benenti, S. (Symmetry, Integrability and Geometry: Methods and Applications, 2016)
An outline of the basic Riemannian structures underlying the separation of variables in the Hamilton-Jacobi equation of natural Hamiltonian systems.